Energy and cost analysis of weight reduction using composite brake rotor - Maleque, Md. Abdul; Adebisi, Adetayo A.; Shah, Qasim Hussain (MechAero Foundation for Technical Research & Education Excellence, 2012)
This paper attempts to predict the effect of weight reduction on energy consumption and cost savings using an aluminium matrix composite automotive brake rotor. Mathematical models are established to evaluate the influence of weight reduction on material consumption, cost and energy savings. The study showed that a 50% weight reduction due to AMC brake rotor replacement compensates for 19% of energy savings against cast iron brake rotor.